Increased functional connectivity following ingestion of dried bonito soup - Satake, Takatoshi; Taki, Ai; Ouchi, Kazuya; Kasahara, Kazumi; Tsurugizawa, Tomokazu (Frontiers in Nutrition, 2024)
Soup, including dried bonito broth, is customarily consumed as an umami taste during meals in Japan. Previous functional magnetic resonance imaging (fMRI) studies have investigated neuronal activation following human exposure to carbohydrates and umami substances. However, neuronal activity following ingestion of dried bonito soup has not been investigated. Additionally, recent progress in fMRI has enabled us to investigate the functional connectivity between two anatomically separated regions, such as the default mode network. In this study, we first investigated the altered functional connectivity after ingesting dried bonito soup in healthy volunteers. Functional connectivity in several brain regions, including the connection between the vermis, part of the cerebellum, and bilateral central opercular cortex, was markedly increased after ingesting dried bonito soup, compared to the ingestion of hot water. Physiological scaling showed that satiety was substantially increased by ingesting hot water rather than dried bonito soup. These results indicate that increased functional connectivity reflects the post-ingestive information pathway of dried bonito soup.